PENGARUH PEMBERIAN INSENTIF DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS LINGKUNGAN HIDUP KABUPATEN BOGOR - Syaiful Anwar; Yasnimar Ilyas; Andhika Gilang Pratama (Institut Teknologi dan Bisnis Dewantara, 2026)
The results of the study indicate that partially, the provision of incentives has a significant effect on employee performance, with a calculated t value of 4.240 > t table 1.997 and a significance value of 0.000 < 0.05. Motivation also has a significant effect on employee performance, with a calculated t value of 3.242 > t table 1.997 and a significance value of 0.002 < 0.05. Simultaneously, the provision of incentives and motivation has a significant effect on employee performance, with a calculated F value of 19.577 > F table 2.478 and a significance value of 0.000 < 0.05. The coefficient of determination (Adjusted R²) value of 0.371 indicates that 37.1% of employee performance is influenced by the provision of incentives and motivation, while the remaining 62.9% is influenced by other variables outside this study. The variable that has a dominant effect on employee performance is the provision of incentives with a regression coefficient value of 0.413. The results of this study indicate the importance of implementing an appropriate incentive system and effective motivation programs in order to improve employee performance.